2015
DOI: 10.1007/s40266-015-0257-x
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Inappropriate Anticholinergic Medication Use in Community-Dwelling Older Adults: A National Cross-Sectional Study

Abstract: The study found that approximately one in ten older adults used potentially inappropriate anticholinergic medications. Several predisposing, enabling and need factors were associated with the use of potentially inappropriate anticholinergic medications. Concerted efforts are needed to optimize potentially inappropriate anticholinergic medication use in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 46 publications
0
45
1
Order By: Relevance
“…The prevalence of visits with any anticholinergics prescribed was stable over time, increasing minimally from 6.1% in 2006–07 to 6.8% in 2008–09 and then decreasing to 4.7% in 2014–15. These rates are slightly lower than that of a previous study using 2009–10 Medical Expenditure Panel Survey, which reported a prevalence rate of 9.6% . These marginal differences may be due to differences in data collection (e.g., individual vs visit level) or which medications were specifically included.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The prevalence of visits with any anticholinergics prescribed was stable over time, increasing minimally from 6.1% in 2006–07 to 6.8% in 2008–09 and then decreasing to 4.7% in 2014–15. These rates are slightly lower than that of a previous study using 2009–10 Medical Expenditure Panel Survey, which reported a prevalence rate of 9.6% . These marginal differences may be due to differences in data collection (e.g., individual vs visit level) or which medications were specifically included.…”
Section: Discussioncontrasting
confidence: 68%
“…On the basis of a strong recommendation grounded in systematic reviews of clinical studies, these 35 anticholinergic drugs are to be avoided regardless of indication . Previous studies investigated anticholinergic use at the national level but relied on self‐reported survey questionnaires from civilians and used old data and older versions of the Beers criteria . Furthermore, these studies were conducted cross‐sectionally such that they did not investigate secular trends of prescribing over time.…”
mentioning
confidence: 99%
“…In international studies on community‐dwelling older adults, the prevalence of PIM use ranges from 9.6%–45.8% (Bazargan et al, ; Kachru et al, ; Lu et al, ). In Brazil, investigations conducted at different locations have reported varying results regarding PIM use (Bazargan et al, ; Kachru et al, ; Lu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In international studies on community‐dwelling older adults, the prevalence of PIM use ranges from 9.6%–45.8% (Bazargan et al, ; Kachru et al, ; Lu et al, ). In Brazil, investigations conducted at different locations have reported varying results regarding PIM use (Bazargan et al, ; Kachru et al, ; Lu et al, ). A study on older adults living in São Paulo (SP) identified a 28% prevalence of PIM, with associated factors being the use of five or more medications ( p = 0.001), the presence of two or more diseases ( p = 0.011) and female gender ( p = 0.007) (Cassoni et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Anticholinergics, used by 10-27% of older adults,123 manage diverse health conditions such as overactive bladder, seasonal allergies, and depression. It is well established that these drugs can cause temporary short term impairment in cognition, including attention and reaction time 4.…”
mentioning
confidence: 99%